Cover Picture: Identification and Classification of Technical Lignins by means of Principle Component Analysis and k‐Nearest Neighbor Algorithm (Chemistry ‐ Methods 8/2021). Issue 8 (5th August 2021) - Fink, Friedrich; Emmerling, Franziska; Falkenhagen, Jana
Abstract : The Front Cover shows an artistic map like those found in many novels. The rivers serve as natural borders to separate different types of plants, such as softwood, hardwood, straw and grass. The idea for this abstract illustration comes from the core illustration of the work on which it is based. With the help of algorithms for data analysis, infrared data of different technical lignins could be successfully evaluated. Subsequently, by creating artificial borders, a predictive model for classifying the lignins according to their original biomass could be created. This represents a fast and efficient method for identifying technical lignins that could be used in handheld devices in the future. More information can be found in the Full Paper by Friedrich Fink et al .